[Rezension von: Play, Pain and Religion: Creating Gestalt through Kink Encounter By A. Robertson (2021)] - Musselman, Cody (Body and religion, 2022)
Play, Pain and Religion: Creating Gestalt through Kink Encounter By A. Robertson (2021) Bristol: Equinox, ix + 213pp., 15 figures